Characterization of the structural, mechanical, and electronic properties of fullerene mixtures: a molecular simulations description12. Issue 14 (13th October 2017) - Tummala, Naga Rajesh; Aziz, Saadullah G.; Coropceanu, Veaceslav; Bredas, Jean-Luc
Abstract : We investigate mixtures of fullerenes and fullerene derivatives, the most commonly used electron accepting materials in organic solar cells, by using a combination of molecular dynamics and density functional theory methods. Abstract : We investigate mixtures of fullerenes and fullerene derivatives, the most commonly used electron accepting materials in organic solar cells, by using a combination of molecular dynamics and density functional theory methods. Our goal is to describe how mixing affects the molecular packing, mechanical properties, and electronic parameters (site energy disorder, electronic couplings) of interest for solar-cell applications. Specifically, we consider mixtures of: (i) C60 and C70 ; (ii) C60, C70, and C84, and (iii) PC61 BM and PC71 BM.